An integrative review of the antecedents and consequences of lateral hiring. Issue 7 (13th July 2015) - Amankwah-Amoah, Joseph
Abstract : Purpose: – Although there is a burgeoning stream of research on lateral hiring (LH), lack of integration of the literature has obscured the past accomplishments and future directions remain unclear. The purpose of this paper is to review and synthesise the existing literature on LH in the spirit of further development of this field. Design/methodology/approach: – The paper is based on an extensive review of the literature across multiple social science disciplines. Findings: – The study integrates the existing streams of research in such a way that human resources and personnel practitioners see the relevance of research and how they can mitigate the negative effects of LH. The study demonstrates how employers can acquire, develop and retain scarce human capital (HC) to help improve their competitiveness. Research limitations/implications: – The main limitation of the review is that the search might have overlooked studies that employed specialised terminologies or keywords not used here. Practical implications: – The study outlines a number of implications for theory and human resource management. Originality/value: – This study advances research on LH by developing an integrated conceptual framework of how the attributes of the target employee, current employer and potential employer influence how LH is considered, instigated, responded to and accepted. The findings highlight the increasingly important role played by HC in developing sustainable competitive advantage.